Market Service Retribution Optimization Strategy through the Root Cause Approach - Suparmono Suparmono; Junaidi Junaidi; Suryanto Suryanto (Telaah Bisnis, 2022)
This article aims to analyze the problems that occur in the non-optimal acceptance of market service retribution and design optimization strategies in Kebumen Regency, Central Java Province. The analytical tool used to analyze the main problem is to use a root cause analysis (RCA) approach and SWOT Analysis. After being analyzed using RCA, the next step is to map out possible strategies to be applied in overcoming these problems with internal and external approaches. From the results of the analysis, it was found that the acceptance of market service retribution was not optimal due to the low awareness of traders in paying levies, the decline in economic activity due to the impact of the pandemic, and the development of modern markets whose regulation was a little late. On the other hand, the development of information technology has resulted in changes in people's shopping patterns through online shopping. This condition certainly needs to be overcome with the right strategy from the government while maintaining healthy competition and controlling modern market outlets. The contribution of this research is that the analysis is carried out comprehensively using several approaches, which are different from previous studies.